Cuisine and symbolic capital : food in film and literature - Mahar, Cheleen. (Cambridge Scholars, 2010)
This collection of interdisciplinary essays examines food as it mediates social relationships and self-presentation in a variety of international films and literature. Authors explore the ways that making, eating and thinking about food reveals culture.